Observation of pentacarbonylchromium on flash photolysis of exacarbonylchromium in cyclohexane solution - KELLY, JOHN MOFFAT (My University, 1973)
The first observable transient (lifetime > 50 ns) on flash photolysis of Cr(CO), is Cr(CO),, which is the precursor of two species previously assigned to the D,, and C,, forms of Cr(CO),, and now shown to arise from reaction with impurities.
PUBLISHED
Keywords: observable transient; observable transient